2017
DOI: 10.4049/jimmunol.1700401
|View full text |Cite
|
Sign up to set email alerts
|

Type I IFN Is Necessary and Sufficient for Inflammation-Induced Red Blood Cell Alloimmunization in Mice

Abstract: During RBC transfusion, production of alloantibodies against RBC non-ABO Ags can cause hemolytic transfusion reactions and limit availability of compatible blood products, resulting in anemia-associated morbidity and mortality. Multiple studies have established that certain inflammatory disorders and inflammatory stimuli promote alloimmune responses to RBC Ags. However, the molecular mechanisms underlying these findings are poorly understood. Type I IFNs (IFN-α/β) are induced in inflammatory conditions associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
64
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(72 citation statements)
references
References 67 publications
8
64
0
Order By: Relevance
“…CD64 expression is typically observed in response to IFNγ stimulation of monocytes, and recent in vitro data has shown that IFNα/β suppresses IFNγ responses in macrophages, leading to CD64 downregulation . Although we did not find differences in measured IFNγ levels between responders and non‐responders, our findings in sickle cell patients may be consistent with recent work from our laboratory showing that IFNα/β impacts the ability of a murine transfusion recipient to form RBC alloantibodies to the KEL human blood group antigen expressed on murine RBCs . Taken together, these data suggest that alloimmunized patients with SCD may have higher IFNα/β levels that prevent IFNγ from leading to the same increase in CD64 expression as would be seen in the absence of IFNα/β.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…CD64 expression is typically observed in response to IFNγ stimulation of monocytes, and recent in vitro data has shown that IFNα/β suppresses IFNγ responses in macrophages, leading to CD64 downregulation . Although we did not find differences in measured IFNγ levels between responders and non‐responders, our findings in sickle cell patients may be consistent with recent work from our laboratory showing that IFNα/β impacts the ability of a murine transfusion recipient to form RBC alloantibodies to the KEL human blood group antigen expressed on murine RBCs . Taken together, these data suggest that alloimmunized patients with SCD may have higher IFNα/β levels that prevent IFNγ from leading to the same increase in CD64 expression as would be seen in the absence of IFNα/β.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, studies in an animal model related IFNα/β and RBC alloimmunization, with exogenous IFNα/β increasing the likelihood of a transfusion recipient becoming alloimmunized. Further, recipients lacking type 1 IFN receptors failed to become alloimmunized . Other cytokine genes also have been shown to be more prevalent in alloimmunized patients with SCD compared to non‐alloimmunized patients …”
mentioning
confidence: 99%
“…Multiple studies have also described a close association between RBC alloantibodies and RBC autoantibodies (Dhawan et al , ; Nickel et al , ). Animal studies (Gibb et al , ,b) suggest that a potential unifying hypothesis for the connection between some types of autoimmunity (Crow, ) and alloimmunization may involve type 1 interferon signalling.…”
Section: Discussionmentioning
confidence: 99%
“…IFNs are critical for host defence against viruses and the literature suggests that they are important mediators of autoimmune disease (Niewold, ). Interestingly, Gibb et al (,) found that type 1 IFNs are necessary to promote alloimmunization in mice. As the SNP we tested is an intergenic variant, its role in influencing the ability of IFN receptor to sense type 1 IFNs is unknown.…”
Section: Discussionmentioning
confidence: 99%